Notable Latin American women : twenty-nine leaders, rebels, poets, battlers and spies, 1500-1900 - Adams, Jerome R., 1938- (McFarland & Co., 1995)
"Straightforward and brief biographical sketches of 29 women including Doña Marina, Juana Inés de la Cruz, Manuela Sáenz, and Leopoldina of Brazil"--Handbook of Latin American Studies, v. 58.